Eosinophil and Eosinophil Cationic Protein Level Raising in Dermatitis Due to Food Patients - Umborowati, Menul Ayu; Sawitri, Sawitri; Hoetomo, Marsoedi (Faculty Of Medicine Airlangga University, 2015)
Background: Food allergy prevalence worldwide has been increase. Skin is secondary most often target organ in food allergy reaction. Food allergy affects 35% atopic dermatitis (AD) patients. Diagnosis of food allergyÂ is still challenge because signs are not speciï¬c. Previous researches showed eosinophil and eosinophil cationic protein (ECP) role in food allergy reaction on gastrointestinal tract, but none on dermatitis due to food. Purpose: To evaluate eosinophil and serum ECP in dermatitis due to food. Method: This is a descriptive observational cross sectional study, with dermatitis due to food patients in Dermatovenereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya as subjects. Subjects has been collected trough consecutive sampling during 3 months, then data were analysized descriptively Results: Serum ECP level of dermatitis due to food patients were above normal range in all subjects, with mean level 108.5 Âµg/L, lowest level 33.011 Âµg/L and higher level 284.849 Âµg/L. Mean eosinophil of dermatitis due to food patients just arise above normal limit (0.413Âµg/L). AD patients were 48.4% among all subjects. Mean serum ECP level of AD patients was higher (121.703 Âµg/L) than non-AD (96.123 Âµg/L). Conclusions: Eosinophil and ECP seems have role in dermatitis due to food pathogenesis. Serum ECP examination can be beneï¬ts to monitor dermatitis due to food severity.Key words: dermatitis due to food, eosinophil, serum eosinophil cationic protein.